Predictive value of gamma-glutamyltransferase for ventricular arrhythmias and cardiovascular mortality in implantable cardioverter-defibrillator patients - You Zhou (BMC Cardiovascular Disorders, 2019)
Abstract Background Gamma-glutamyltransferase (GGT) is a new predictor of cardiovascular diseases. In this study, we aimed to determine its association with ventricular arrhythmias (VAs) in implantable cardioverter-defibrillator (ICD) patients. Methods One hundred and forty patients implanted with ICD or cardiac resynchronization therapy defibrillator with home monitoring were studied retrospectively. The primary endpoint was appropriate ICD treatment of VAs, secondary endpoint was cardiac death. Results During a mean follow-up period of 44 ± 17 months, 78 patients (55.7%) experienced VAs, 50 patients (35.7%) were treated with appropriate ICD shocks and 16 patients (11.4%) died due to cardiovascular diseases. GGT was positively correlated with high sensitivity C reactive protein (r = 0.482, P < 0.001), left ventricular end-diastolic dimension (r = 0.175, P = 0.039), New York Heart Association class (r = 0.199, P = 0.018), fasting blood glucose (r = 0.233, P = 0.006) and negatively with left ventricular ejection fraction (r = − 0.181, P = 0.032) and high-density lipoprotein (r = − 0.313, P < 0.001). Based on receiver operating characteristics curve, the cut-off value of GGT = 56 U/L was identified to predict VAs. In Kaplan-Meier survival analysis, GGT ≥56 U/L was associated with increased VAs (P<0.001), ICD shock events (P = 0.006) and cardiovascular mortality (P = 0.003). In multivariate COX regression models, GGT ≥56 U/L was an independent risk factor for VAs (HR 2.253, 95%CI:1.383–3.671, P = 0.001), ICD shocks (HR 2.256, 95%CI:1.219–4.176, P = 0.010) and cardiac death (HR 3.555, 95%CI:1.215–10.404, P = 0.021). Conclusions In this ICD population, GGT ≥56 U/L was independently associated with VAs and cardiac death.